Exploring the Psychological Stress, Anxiety Factors, and Coping Mechanisms of Critical Care Unit Nurses During the COVID-19 Outbreak in Saudi Arabia - Ali, Shaimaa Ahmed Awad; Diab, Samar Salah Eldin Mohamed; Elmahallawy, Ehab Kotb (Frontiers in Public Health, 2021)
Background: The spread of coronavirus disease 2019 (COVID-19) throughout the world has resulted in a series of modifications of several National Health Service organizations, with a potential series of psychological consequences among nurses. Methods: The present study was undertaken to assess the psychological stress, anxiety factors, and coping mechanisms in critical care unit nurses during the COVID-19 outbreak. A cross-sectional research design was employed and the convenience sample consisted of 469 nurses who worked at several hospitals in Saudi Arabia during the period from July to September 2020. The study used the Generalized Anxiety Disorder, Coping Mechanism, and Nursing Stress scale. Results: Interestingly, more than one-third and one-quarter of the studied nurses had severe anxiety and moderate anxiety levels, respectively. In addition, the factors causing the most anxiety were providing care for their infected colleagues and worrying about infecting their families. More than one-quarter and slightly less than half of the studied nurses had high and moderate stress levels, respectively. Furthermore, more than half of the participants had low coping mechanisms and one-quarter had moderate coping mechanisms. In addition, there was a strong positive correlation between anxiety and stress levels, and there was a strong negative correlation between coping mechanisms and stress and anxiety levels. Conclusions: Collectively, the present study explored the psychological stress, anxiety factors, and coping mechanisms among nurses during the COVID-19 outbreak in critical care units in Saudi Arabia. Continuous educational programs for nurses on using coping mechanisms should be developed combined with teaching preventive measures and defining a psychological intervention plan within a mandatory occupational health surveillance program. The current study recommends that constructive planning and necessary provision of supportive measures ‎by ‎the ‎legal authorities and policy makers in order to protect the nurses and minimize psychological stress to fulfill ‎high-quality nursing ‎care.‎ ‎